Spontaneous thoracolumbar spinal cord infarction: report of six cases. - Monteiro, L; Leite, I; Pinto, J; Stocker, A (1992)
We present a retrospective study of 6 patients with spinal cord infarction in the territory of the Adamkiewicz artery. In all patients, the clinical picture was stereotyped: sudden onset of paraplegia and bilateral radicular pain, dissociated sensory loss below the level of infarction and sphincter dysfunction. Emergency neuroradiological investigation ruled out a compressive lesion in all cases. In one patient, spinal angiography was performed and identified an occlusion of the Adamkiewicz artery. Treatment was supportive and all patients had a substantial recovery over a period of weeks.